Comparative Study Between Gemcitabine-Based and Gemcitabine Plus S1–Based Preoperative Chemoradiotherapy for Localized Pancreatic Ductal Adenocarcinoma, With Special Attention to Initially Locally Advanced Unresectable Tumor. Issue 2 (February 2019) - Takeuchi, Taijiro; Mizuno, Shugo; Murata, Yasuhiro; Hayasaki, Aoi; Kishiwada, Masashi; Fujii, Takehiro; Iizawa, Yusuke; Kato, Hiroyuki; Tanemura, Akihiro; Kuriyama, Naohisa; Azumi, Yoshinori; Usui, Masanobu; et al.
Abstract : Objectives: To evaluate clinical/histological response and prognosis between preoperative gemcitabine-based chemoradiation therapy (G-CRT) and gemcitabine plus S1–based CRT (GS-CRT) for localized pancreatic ductal adenocarcinoma patients according to the 3 resectability groups. Methods: Among 199 patients who had 90% or more relative dose intensity of chemotherapy and completion of radiotherapy preoperatively (G-CRT: 98 and GS-CRT: 101), the subjects were 113 patients (G-CRT: 60 and GS-CRT: 53) who underwent curative-intent resection, and we compared clinical and histological effects between the 2 regimens. Results: There is a significant improvement in clinical and histological responses as assessed by reduction rate in tumor size, post-CRT serum level of carbohydrate antigen 19-9, and the ratio of histological high responder according to the Evans grading system in GS-CRT, as compared with G-CRT, which in turn significantly increased R0 resection rate ( P = 0.013). These effects of GS-CRT resulted in significant improvement of disease-specific survival (median survival time, 36.0 vs 27.2 months; P = 0.042), especially in patients with unresectable locally advanced disease (36.0 vs 18.1 months, P = 0.014). Conclusions: For localized pancreatic ductal adenocarcinoma patients, GS-CRT, as compared with G-CRT, provides significant improvement in clinical and histological response as well as long-time survival, especially in patients with unresectable locally advanced disease.